Credit securitization and credit derivatives: Financial instruments and the credit risk management of middle market commercial loan portfolios - Sabine Henke; Hans-Peter Burghof; Bernd Rudolph (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
Banks increasingly recognize the need to measure and manage the credit risk of their loans on a portfolio basis. We address the subportfolio middle market. Due to their specific lending policy for this market segment it is an important task for banks to systematically identify regional and industrial credit concentrations and reduce the detected concentrations through diversification. In recent years, the development of markets for credit securitization and credit derivatives has provided new credit risk management tools. However, in the addressed market segment adverse selection and moral hazard problems are quite severe. A potential successful application of credit securitization and credit derivatives for managing credit risk of middle market commercial loan portfolios depends on the development of incentive-compatible structures which solve or at least mitigate the adverse selection and moral hazard problems. In this paper we identify a number of general requirements and describe two possible solution concepts.
urn:nbn:de:hebis:30-9462
Keywords: G21; G11; 330; credit derivatives; credit risk management; securitization